FORAMINIFERA AND ASSOCIATED ENVIRONMENTS OF BAHÍA INGLESA, NORTH-CENTRAL CHILE (27°S) - Berger, Rachel Lynn (OpenSIUC, 2010)
A total of 24 Neogene sediment samples were collected near Bahía Inglesa (27° 07' 40.78'' S, 70° 50' 41.47'' W and 27°07' 44.90'' S, 70° 50' 46.06'' W), north-central Chile during the summer of 2004. Neogene sediment has previously been recognized in this region by Godoy et al., (2003). Using standard laboratory techniques, samples were processed for both planktonic and benthic foraminifera. Statistical analyses were used on benthic foraminiferal data to infer paleodepositional environment and relative water depth. Planktonic foraminifera, when present, were used to establish a general age for samples; no planktonic foraminifera were found in sediments collected from the northern section sampled. Planktonic foraminifera found in the southern section indicate a Middle Miocene age (11.4 to 15 Ma). Statistical analyses of benthic foraminifera showed the presence of one foraminiferal assemblage for the northern section, Rocas Negras North (RCN) and produced two assemblages for the southern section, Rocas Negras South (RCS). RCN is interpreted to be a stable upper middle bathyal environment (< 1,000 m water depth) while RCS ranges in water depth from inner shelf (<50 m) to upper bathyal water depths (165-302 m). A difference in environments between localities is attributed to the location of sample sites relative to a NNE-SSW trending normal fault that separates them. Both localities shallow upwards, which is consistent with widely accepted ideas of a decrease in global temperatures and a general decline in eustatic sea level throughout the Neogene.